Medical error as a basis for legal responsibility of physicians and health facilities - Počuča, Milan B; Šarkić, Nebojša N; Mrvić-Petrović, Nataša V (Vojnosanitetski pregled, 2017)
Key words: medical errors; physician-patient relations; health facilities; ethics, medical; jurisprudence; legislation.